Arthroscopic Assisted Resection of Triangular Fibrocartilage Complex Lesions: A 19-Year Follow-up. (May 2018) - Soreide, Endre; Haugstvedt, Jan-Ragnar; Husby, Torstein
Background: This study assesses long-term functional and subjective outcomes following arthroscopic assisted resection of lesions of the triangular fibrocartilage complex (TFCC).Methods: Functional and subjective outcomes were assessed based on review of patient charts for patient demographic characteristics, comprehensive clinical evaluation, obtained radiographs, and patient-reported questionnaires.Results: Fifteen patients, of whom 9 were female, and 10 dominant wrists, were included in this study. Median age was 60 (range, 37-73) years, and median duration of follow-up was 19 (range, 18-21) years. Median Mayo Wrist Score was 85 (range, 45-100). Four patients scored excellent, 7 good, 3 fair, and 1 poor result according to the Modified Mayo Wrist Score. Median Quick Disabilities of the Arm, Shoulder and Arm was 20 (range, 0-45) and Patient-Rated Wrist and Hand Evaluation was 8 (range, 0-61). Patients reported high rate for satisfaction and low rate for pain. All patients presented intact stability of the distal radioulnar joint.Conclusions: This study demonstrates persisting satisfactory subjective and functional outcomes for patients following arthroscopic assisted resection for lesions of the TFCC at 19 years of follow-up. Arthroscopically assisted resection of selected TFCC lesions seems to be both a safe and efficient procedure.